Recycling‐Induced Copper Contamination of a 42CrMo4 Quench and Tempering Steel: Alterations in Transformation Behavior and Mechanical Properties. Issue 3 (28th November 2022) - Gramlich, Alexander; Hinrichs, Torben; Springer, Hauke; Krupp, Ulrich
Abstract : The transformation behavior and the mechanical properties of three laboratory produced steels are presented. To investigate the influence of copper contamination, the reference alloy 42CrMo4 is modified and alloyed with 0.5 and 1.0 wt% copper, respectively. The transformation behavior is investigated through dilatometry that yields continuous cooling transformation diagrams, while the mechanical properties are investigated by hardness measurements as well as Charpy‐V‐notch impact and tensile tests. Accompanying microstructure investigations by means of light optical, scanning electron, and transmissions electron microscopy and thermodynamic simulations (CALPHAD) are performed. It is demonstrated that copper contamination that will be unavoidable when increasing the overall steel recycling fraction may contain the potential for increasing the hardness as well the strength of standard high strength steels, although it is considered to be very detrimental during steel production. Together with reduced environmental footprints and production costs due to the utilization of lower grade scrap with more Cu‐contamination, the development of alternative processing routes for Cu‐contamination‐tolerant high strength steels is pursued. Abstract : Copper impurities caused by recycling are simulated by adding Cu to a standard quenched and tempered steel. It is demonstrated that impurities can be used to increase mechanical properties. Accordingly, it can be assumed that the recycling‐induced increase of Cu in steel shall not generally be considered negative if the problem of hot shortness can be remedied in the future.